ANALYSIS OF RISK FACTORS ASSOCIATED WITH DIARRHEA IN WORK AREA HEALTH DISTRICT CHARMING CITY Sidomulyo PEKANBARU - Chairil, - (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Diarrhea is one of the diseases that get priority eradication program because of the high morbidity and caused many deaths. In an effort to decrease the morbidity due to diarrhea important to know the factors that become menyebab incidence of the disease include the state of the environment, disease vector, personal hygiene, snack habits, and health services. The research was done at Village West Sidomulyo Tuah Karya and Sidomulyo subdistrict Puskesmas Handsome that during the period of the last 4-6 months of diarrhea always get into the top 10 diseases. The research objective was to determine the relationship between risk factors with the incidence of diarrhea. The study was a cross sectional study, using a questionnaire. Sampling was done by randomsampling, some 96 respondents. Results of research for the environmental health situation no association with diarrhea because of the test results chi-square statistic with continuity correction values obtained p = (1.00)> Î± = (0.05), disease-carrying vector no association with diarrhea because of test results chi-square statistic with continuity correction values obtained p = (1.00)> Î± = (0.05), there is no relationship between personal hygiene with diarrhea, because of the results of statistical chi-square test with continuity correction values obtained p = (0.69)> Î± = (0.05), there was no relationship between snacks at roadside with diarrhea, because of the results of statistical chi-square test with continuity correction values obtained p = (1.00)> Î± = (0, 05) there is no relationship between counseling with diarrhea, because of the results of statistical chi-square test with continuity correction values obtained p = (0.42)> Î± = (0.05), the variables being researched nothing to do with diarrhea , but it diskritif there, it is to note could be a risk for diarrhea will occur, it is necessary to promotive and preventive efforts.